The practice of educational research from psychology: implied interest and social purpose - Carrasco Aguilar, Claudia (Revista de Psicología, 2010)
This article seeks to develop the thesis that the Psychology and Education can be linked in the field of Educational Research, by means of a relationship that does not fall into any of these disciplines in a relationship of domination on the other. Traditionally, the Psychology has been placed at the service of the interests of social reproduction of Education, working with its maintenance through strategies of validation arising from the forms of scientific research. However, we are currently at a scenario which the innovations and ethical questions and politicians to these forms of approaching phenomenon educational, are beginning to evident with greater force, demonstrating that there practical experiences from methodologies as the systematization of experiences and Research Action, who collaborate with the questioning of the social function of the Educational Research from the psychological intervention, with a purpose last social emancipation.